’’Real rape’’ stereotype: Between knowledge and beliefs - Lajić, Oliver; Baić, Valentina; Tomić, Marta (NBP. Nauka, bezbednosti, policija, 2022)
The paper presents the results of a research related to the existence of stereotypes in connection with sexual violence among the general population of Serbia, as well as among the students of the University of Crime Investigation and Police Studies in Belgrade (hereinafter: KPU). Bearing in mind that comparative studies testify to a high level of presence of stereotypes related to sexual violence, the researchers attempted to establish whether there are any differences in the understanding of this issue among the abovementioned categories of respondents, as some of them are prospective police officers, who will likely be in contact with the victims of sexual violence given the nature of their job. The focus was also on the differences in the manner of obtaining information about this phenomenon. The study encompassed a total of 310 respondents, out of whom 62 were the students of the KPU and 61 students of other universities, whereas all others were older than student age. Data were collected by filling in a questionnaire and analysing responses by the use of descriptive statistics and correlation. The results suggest that the information from the Internet is a principal source of obtaining information about sexual violence except among the KPU students, who primarily learn about such phenomena from professional literature. The initial thesis on the absence of significant differences related to rape stereotypes among the KPU students and students of other universities, irrespective of their previous professional education, has been confirmed, which indicates the need for narrowly targeted expert education of prospective police officers in respect of issues of sexual violence.